CeO2/Cr2O3 direct Z-scheme heterojunction for photo-thermal synergistic catalytic isopropanol degradation and nitrogen fixation. Issue 2 (8th December 2022) - Zhou, Kun; Sun, Hao; Liu, Yajing; Wang, Qian; Liu, Bin; Li, Dongke; Zhao, Hongming; Tao, Ran; Fan, Xiaoxing
Abstract : Direct Z-scheme CeO2 /Cr2 O3 with oxygen vacancies is successfully prepared. The photothermal synergy in direct Z-scheme CeO2 /Cr2 O3 could improve the nitrogen fixation and isopropanol degradation activities. Abstract : A CeO2 /Cr2 O3 composite heterojunction material is prepared by the combination of a water bath method and a high temperature calcination method. The CeO2 /Cr2 O3 composite shows enhanced photo-thermal synergistic catalytic activity in comparison with single component Cr2 O3 and CeO2 . The photo-thermal catalytic nitrogen fixation rate of the CeO2 /Cr2 O3 composite is 21.0 times that of Cr2 O3 and 11.7 times that of CeO2 . The photo-thermal catalytic isopropanol degradation rate of the CeO2 /Cr2 O3 composite is 1.3 times that of Cr2 O3 and 3.0 times that of CeO2 . The improved catalytic activity of the CeO2 /Cr2 O3 composite is attributed to the following three points. The CeO2 /Cr2 O3 heterojunction exhibits a Z-scheme charge transfer mechanism, and the photo-generated carriers have a strong redox ability. There are abundant oxygen vacancies in the CeO2 /Cr2 O3 composite, which can form a new impurity level leading to the weakening of carrier recombination. The CeO2 /Cr2 O3 composite has a large specific surface area, which can provide more catalytically reactive sites. Moreover, the photo-thermal catalytic isopropanol degradation activity of CeO2 /Cr2 O3 has no significant decrease after four cycle experiments, proving its good stability. This study inspires the design and construction of efficient photo-thermal catalysts in the field of air purification and energy conversion.